Populational fluctuation of Willistoniella Mik and Ropalomera Wiedemann (Diptera: Ropalomeridae) in the Central Amazonia - Marques, Ana Paula Coelho; Ale-Rocha, Rosaly; Ronchi-Teles, Beatriz (Neotropical Entomology, 2004)
The populational fluctuation of flies of the genera Willistoniella Mik and Ropalomera Wiedemann (Diptera: Ropalomeridae) was studied using McPhail traps, with molasses (10%) as attractive bait, in two places in a mixed orchard of the families Myrtaceae, Sapotaceae, Anacardiaceae, Apocinaceae and Gutiferae, during 13 months (december of 1996 to december of 1997) in the Central Amazonia, Brazil. The total of 1,148 Willistoniella flies and 99 Ropalomera flies were captured. The abundance observed in the genera was larger during the dry months, however there was no correlation between flies caught in the traps and the rainfall in the two places.
Flutuação populacional de Willistoniella Mik e Ropalomera Wiedemann (Diptera: Ropalomeridae) na Amazônia Central
Keywords: Anacardiaceae; Diptera; Insecta; Myrtaceae; Ropalomera; Ropalomeridae; Sapotaceae; Willistoniella